Systems in english grammar - Master, Peter (Prentice Hall Regents, 1995)
This book teaches teachers how to present grammar lessons to their students with confidence and clarity. Introduces future teachers of English to the major elements of English grammar in a systematic fashion, using step-by-step procedures, charts, diagrams, and exercises. Includes a complete answer key to exercises. Grammar teachers.